PENERAPAN KEPEMIMPINAN KOLABORASI KEPADA KEPALA UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Aryani, Refi Meilia; Haryadi, Rudi (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to analyze the application of collaborative leadership by school principals in improving school learning quality. The research method used is a literature study by collecting data from reliable sources such as scientific journals, books, and official publications. The results show that collaborative leadership can improve the quality of learning by strengthening cooperation and communication between principals, teachers, and students. In collaborative leadership, the principal is a facilitator who encourages active participation from all parties in the decision-making process and program implementation. In addition, principals can also create a school culture that supports collaboration and facilitates teachers' professional development. Recommendations include the importance of collaborative leadership training for principals, the development of a school culture that supports collaboration, and rewards for active participation in the collaborative process.